The Impact of Applying the Accounting Islamic Standards on the Cost Efficiency: An applied study in kingdom of Bahrain Islamic banks -Wholesale (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research highlights the light on the general framework of accounting discloser in the Islamic banks, and show the types and the concepts of Cost Efficiency, In this present study, the sample included Fourteen Islamic banks, where the data was collected from the annual financial reports. Accordingly, the study in order to achieve the aims and access to the results based on the analytical method and the descriptive analysis, and conducted a Simple & Multiple Linear Regression analysis, in order to test hypotheses of the research by using of statistical analysis software (SPSS). The research has arrived to many results such as: the commitment of Islamic banks working in the Kingdome of Bahrain (Wholesale) to the requirements of the general standard of presentation and disclosure for Islamic financial institutions contributes to provide financial statement that relevant with a perfect accounting system, and to contribute to reduce the costs and increase the investments because the high confidence of investors. Also the Islamic banks working in the Kingdom of Bahrain (Wholesale) are committed to the requirements of the general standard of presentation and disclosure for the Islamic financial institutions, and there is an impact of that commitment on the cost Efficiency in these banks.